PERTANGGUNG JAWABAN MASKAPAI ANGKUTAN UDARA TERHADAP RUSAKNYA BAGASI BERDASARKAN UNDANG – UNDANG NOMOR 1 TAHUN 2009 - Fahmi, Faris; Martono, H. K. (Jurnal Hukum Adigama, 2019)
Transportation is a system that is very helpful for humans in their daily lives, transportation is divided into 3 types, that are land transportation, sea transportation, and air transportation (aircraft). Each type of transportation has different type of vehicles, for land transportation there are motorbikes and cars, sea transportation there is ships, and air transportation there is airplanes. The most efficient type of transportation is air transportation, because it takes the least amount of time for even long distances, therefore people are prefer to use this type of transportation. Air transportation provider or airline must be responsible for any losses incurred during flight activities in accordance with existing regulations. But in fact, there are still problems such as, passenger checked baggage damaged due to flight activities and the one who bears the loss is the passenger, the airline does not respond to this problem and the problem not closed.This journal will discuss about the responsibility system that can be used for the case and how law govern to clear the problem.